Comparison on Applications and Impact of AI in English Grammar Learning - Selvi, V. Thamil; B, Vaishnavi. (Recent Research Reviews Journal, 2024)
English grammar plays an important role in the learning of English language skills. However, it has always been challenging for students to understand grammar right from school. Complicated rules make the learning process even harder. Teachers have tried to come up with many ways to make the learning process interesting and simple yet there exists a gap. Artificial Intelligence bridges the gap and achieves the goal of attaining grammar learning in interesting ways. The integration of artificial intelligence (AI) in grammar learning applications represents a transformative approach to language education. Many applications focus on teaching grammar by gamifying the learning process. AI-powered applications provide personalized learning experiences, immediate corrective feedback, and adaptive difficulty adjustments, leading to improved grammatical competence and sustained user engagement. This research attempts to make a comparative study of English grammar learning platforms and applications by analyzing their impact on the autonomous learning of students. Applying AI has been considered learner-centric as it stimulates learning and fascinates the learners with expected learning outcomes.